2014
DOI: 10.1128/aem.00887-14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Algal Aggregation by Bacillus sp. Strain RP1137

Abstract: Alga-derived biofuels are one of the best alternatives for economically replacing liquid fossil fuels with a fungible renewable energy source. Production of fuel from algae is technically feasible but not yet economically viable. Harvest of dilute algal biomass from the surrounding water remains one of the largest barriers to economic production of algal biofuel. We identified Bacillus sp. strain RP1137 in a previous study and showed that this strain can rapidly aggregate several biofuel-producing algae in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Moreover, there is a basic lack of knowledge on the flocculation mechanisms. However, it is assumed that there are two possible mechanisms for aggregation of microalgae cells by means of bacteria: The first one is based on formation of aggregation via certain polysaccharide and protein compounds produced by bacterial/fungal cell walls [ 57 ], and the second one is a direct linking of the bacteria and microalgae, forming aggregated microalgae cells through charge neutralization reactions/electrostatic patching/bridging by extracellular polymeric substances (EPS) [ 58 ] to enhance sedimentation process of microalgae [ 59 ]. A number of studies propose the possibilities of both bridging and patching mechanisms for aggregation of a large and very close microalgae cells respectively for such bioflocculation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a basic lack of knowledge on the flocculation mechanisms. However, it is assumed that there are two possible mechanisms for aggregation of microalgae cells by means of bacteria: The first one is based on formation of aggregation via certain polysaccharide and protein compounds produced by bacterial/fungal cell walls [ 57 ], and the second one is a direct linking of the bacteria and microalgae, forming aggregated microalgae cells through charge neutralization reactions/electrostatic patching/bridging by extracellular polymeric substances (EPS) [ 58 ] to enhance sedimentation process of microalgae [ 59 ]. A number of studies propose the possibilities of both bridging and patching mechanisms for aggregation of a large and very close microalgae cells respectively for such bioflocculation processes.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria were chosen to represent a diverse range of taxonomic groups, and were isolated from a range of sources, including both natural environments and laboratory-maintained cultures. Marinobacter adhaerens HP 15 WT attaches to and aggregates T. weissflogii (Sonnenschein et al 2012) and Bacillus megaterium has been shown to aggregate N. oceanica (Powell and Hill 2014); hence, both species were included as positive controls. All bacteria were grown in marine broth (BD Difco 279110, Becton Dickinson, USA) at 25°C…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 99%
“…While bacteria may increase aggregation and the stability of aggregates (Heissenberger and Herndl 1994), attached bacteria may also reduce aggregation due to the hydrolysis of phytoplankton surface mucus (Grossart et al 2006a, b). Moreover, the role of heterotrophic bacteria for phytoplankton aggregation can vary appreciably between phytoplankton species (Grossart et al 2006b;Powell and Hill 2013) while the identity of the bacteria can also influence levels of aggregation (Kranck and Milligan 1988;Alldredge and Gotschalk 1989;Riebesell 1991;Alldredge et al 1995;Gärdes et al 2011;Nontembiso et al 2011;Wang et al 2012;Powell and Hill 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the aggregation of both Nannochloropsis oceanica and Bacillus sp. strain RP1137 is dependent on pH and divalent cations, and has been described to occur via neutralization of charge with calcium ions at the cell wall surface of both algae and bacteria [ 69 ].…”
Section: Algae-bacteria Interactions: Current and Promising Applicmentioning
confidence: 99%